ANALISIS PENGARUH KUALITAS PELAYANAN, PERSEPSI HARGA, KUALITAS PRODUK DAN WORD OF MOUTH TERHADAP KEPUTUSAN PEMBELIAN KONSUMEN (STUDI PADA TOKO SENI KERAJINAN MAS & PERAK SULAIMAN INTAN PERMATA DI SEMARANG) - Hidayati, Nur; Tri Astuti, Sri Rahayu (Faculty of Economics and Business Diponegoro University, 2015)
This study aimed to analyze the impact of service quality, perceived price, quality products and Word of Mouth on purchasing decisions in Toko seni kerajinan Mas & perak sulaiman intan Permata at SemarangThe population used is the customers who've purchased the product in Toko Seni Kerajinan Mas & Perak Sulaiman Intan Permata. The amount of sample that is used as much as 100. Then the data were analyzed using multiple regression analysis. This analysis includes the Validity, Reliability Test, Regression Analysis, Classical Assumption Test, Hypothesis Testing through F test and t test, and analysis of the coefficient of determination (R²).Based on the research results, obtained by regression equation: Y = 0,187 X1 + 0,284 X2 +0,234 X3 + 0,320 X4 . All Hypothesistested using t test showed that the variable quality of service,perception of price, quality products and word of mouth is found to significantly affect dependentvariable (purchase decision). Then through the F test can be seen that the independent variablefeasible to test the dependent variable (purchase decision). Result from Adjusted R Square of 0.648 or 64,8% indicates that purchase decision variable can be explained by the variable quality of service, perception of price, quality products and Word of Mouth on purchasing decisions, while the remaining 35.2% is explained by other variables out side the four variables used in the study .